Phytotherapy as the part of the complex treatment of lower urinary tract diseases - G. V. Bachurin (Zaporozhye State Medical University, 2015)
The use of phytotherapy in the treatment of urinary tract diseases has been known for a long time. But at present it has become widely used and got scientific justification for urological pathology, particularly in the treatment of prostatitis. Aim. To investigate the best phytotherapeutic medications for the complex treatment of lower urinary tract diseas. Methods and results. Reasonable combinations of various compatible herbs have been investigated. The best phytotherapeutic medications to reduce inflammation in the prostate have been determined. Conclusion. Phytotherapy should be used only after consulting a phytotherapist in strict compliance with relevant regulations. These regulations provide the duration, the alternation of herbal collections, taking patient age and comorbidities into account, etc.